Effect of use of methyltriethylamonium chloride individually and combined with n-butylamine on the characteristics of the ZSM-12 zeolite crystallization process (Research, Society and Development, 2022)
The improvement of the structure of the ZSM-12 zeolite has been extensively studied, due to its shape selectivity properties, acidity and hydrothermal stability, with this zeolite being used in a wide range of applications, such as adsorbent, ion exchanger and in important reactions in the petrochemical area. In this work, the effect on the crystallization characteristics and physicochemical properties of the ZSM-12 zeolite using methyltriethylammonium chloride, individually, and combined with n-butylamine, as structure-directing agent was studied. The syntheses were carried out at 160 and 170 °C between 48 and 144 h in static medium. The samples obtained were characterized by the techniques of X-ray diffraction, thermal analysis, nitrogen adsorption-desorption and temperature-programmed ammonia desorption. The simultaneous use of methyltriethylammonium chloride and n-butylamine, at a ratio of 0.2, promoted the obtainment of highly crystalline ZSM-12, with an increase in the microporous area and acidity, denoting an improvement in the physicochemical properties of this zeolite.